Considering the economic value of natural design elements at city scale - el-Baghdadi, Omniya; Desha, Cheryl; Hargroves, Charlie (2013)
With increasing signs of climate change and the influence of national and international carbon-related laws and agreements, governments all over the world are grappling with how to rapidly transition to low-carbon living. This includes adapting to the impacts of climate change that are very likely to be experienced due to current emission levels (including extreme weather and sea level changes), and mitigating against further growth in greenhouse gas emissions that are likely to result in further impacts. Internationally, the concept of ‘Biophilic Urbanism’, a term coined by Professors Tim Beatley and Peter Newman to refer to the use of natural elements as design features in urban landscapes, is emerging as a key component in addressing such climate change challenges in rapidly growing urban contexts. However, the economics of incorporating such options is not well understood and requires further attention to underpin a mainstreaming of biophilic urbanism. Indeed, there appears to be an ad hoc, reactionary approach to creating economic arguments for or against the design, installation or maintenance of natural elements such as green walls, green roofs, streetscapes, and parklands. With this issue in mind, this paper will overview research as part of an industry collaborative research project that considers the potential for using a number of environmental economic valuation techniques that have evolved over the last several decades in agricultural and resource economics, to systematically value the economic value of biophilic elements in the urban context. Considering existing literature on environmental economic valuation techniques, the paper highlights opportunities for creating a standardised language for valuing biophilic elements. The conclusions have implications for expanding the field of environmental economic value to support the economic evaluations and planning of the greater use of natural elements in cities. Insights are also noted for the more mature fields of agricultural and resource economics.